(X^2+6x)^2+8(x^2+6x)=9

0 голосов
85 просмотров

(X^2+6x)^2+8(x^2+6x)=9


Алгебра (102 баллов) | 85 просмотров
Дан 1 ответ
0 голосов
Правильный ответ
(x^2+6x)^2+8(x^2+6x)=9

Замена: x^2+6x=t

t^2+8t-9=0

D=8^2-4*1*(-9)=64+36=100

t_1= \frac{-8+10}{2}=1

t_2= \frac{-8-10}{2}=-9

x^{2} +6x=1                                  или          x^{2} +6x=-9

x^{2} +6x-1=0                           или           x^{2} +6x+9=0

D=6^2-4*1*(-1)=40         или        (x+3)^2=0

x_1= \frac{-6+2 \sqrt{10} }{2} =-3+ \sqrt{10}         или       x=-3

x_2= \frac{-6-2 \sqrt{10} }{2} =-3- \sqrt{10}

Ответ: -3б \sqrt{10};  -3

(83.6k баллов)